2022
DOI: 10.1080/23311975.2022.2139213
|View full text |Cite
|
Sign up to set email alerts
|

IFRS adoption, corporate governance and faithful representation of financial reporting quality in Nigeria’s development banks

Abstract: Development banks were designed to achieve the government's economic priorities that were not adequately addressed by the banking industry. Studies, however, show that the activities of some development banks in Nigeria have not been as impacting as expected for different reasons, which include lack of access to finance. This study investigated the impact of International Financial Reporting Standards (IFRS) adoption and corporate governance on the faithful representation of the financial reporting quality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The study revealed a positive association between IFRS and increased audit fees among early adopters, while the impact on late adopters was found to be weak. Ajibade et al (2022) also discovered the significant influence of IFRS adoption and corporate governance on the faithful representation of financial reporting among Nigerian development banks. Due to the unique institutional setting in every African country, coupled with distinct organizational structures and governance procedures, the adoption of IFRS is influenced by firm characteristics, the presence of professional and regulatory accounting bodies and external audit affiliations.…”
Section: Overview Of Ifrs Adoption and Compliance Literature In Africamentioning
confidence: 95%
See 1 more Smart Citation
“…The study revealed a positive association between IFRS and increased audit fees among early adopters, while the impact on late adopters was found to be weak. Ajibade et al (2022) also discovered the significant influence of IFRS adoption and corporate governance on the faithful representation of financial reporting among Nigerian development banks. Due to the unique institutional setting in every African country, coupled with distinct organizational structures and governance procedures, the adoption of IFRS is influenced by firm characteristics, the presence of professional and regulatory accounting bodies and external audit affiliations.…”
Section: Overview Of Ifrs Adoption and Compliance Literature In Africamentioning
confidence: 95%
“…The study revealed a positive association between IFRS and increased audit fees among early adopters, while the impact on late adopters was found to be weak. Ajibade et al. (2022) also discovered the significant influence of IFRS adoption and corporate governance on the faithful representation of financial reporting among Nigerian development banks.…”
Section: Overview Of Ifrs Adoption and Compliance Literature In Africamentioning
confidence: 95%
“…This includes insights into valuation methods, expected performance, and potential risks associated with the instruments. Through this provision, IFRS 17 ensures that investors and participants have access to accurate information when making decisions (Ajibade et al, 2022). Therefore, based on the aforementioned discussion, it can be concluded that IFRS 17 facilitates transparency and accuracy in financial reporting, allowing investors and participants to make informed decisions.…”
Section: Ifrs 17 and Enabling Investors And Participants To Take Deci...mentioning
confidence: 99%